Acesso vascular definitivo em usuários de hemodiálise: construção e validação de uma escala de conhecimento - Pinto, Elda Garbo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Methodological nature study of the construction and validation of assessment tools in health, in order to build and validate knowledge scales about the permanent vascular access in hemodialysis users for nephrology nurses. The steps to prepare the scales were: practices selection involving permanent vascular access to hemodialysis users, theoretical basis of selected practices and development of guided scales in clinical guidelines (guidelines) Clinical practice guidelines for vascular Access, “Guías de Acceso Vascular em Hemodiálisis” (Espanish Society of Nephrology) and “Guía de acceso vascular en hemodialysis”. Thus, four scales were built : knowledge Scale of permanent vascular access in hemodialysis users (KSPVA) – Universal Care, knowledge Scale of permanent vascular access in hemodialysis users (KSPVA) – Specific Care, knowledge Scale of permanent vascular access in hemodialysis users (KSPVA) – physical examination and knowledge Scale of permanent vascular access in hemodialysis users (KSPVA) – Hemodynamic Monitoring. Data collection occurred from February to August 2013, using a questionnaire, consisting of the following parts : trial content (constructo), of the attributes and components of each built scale. The scales content validity was performed by twelve judges with extensive experience in the field of nephrology. All built scales were validated by professionals under minimum favorable consensus of 75 %. It is noteworthy that after validation, scales were applied to 84 nurses, working on renal replacement therapy in 3 centers in towns of São Paulo State, where 2.3% of the professionals have demonstrated little knowledge, 33.3 % have demonstrated satisfactory knowledge and 64.2 % of the professionals have demonstrated full knowledge about care and complications with AVF

Estudo de cunho metodológico de construção e validação de instrumentos de avaliação em saúde, com o objetivo de construir e validar escalas de conhecimento sobre o acesso vascular definitivo em usuários de hemodiálise para os profissionais de enfermagem de nefrologia. As etapas para a elaboração das escalas foram: seleção das práticas envolvendo o acesso vascular definitivo em usuários de hemodiálise, fundamentação teórica das práticas selecionadas e elaboração das escalas pautadas nas diretrizes clínicas (guidelines) Clinical practice guidelines for vascular Access, Guías de Acceso Vascular em Hemodiálisis (Sociedade Espaῆola de Nefrología) e Guía de acceso vascular en hemodiálisis. O produto desse estudo foi a construção de quatro escalas: Escala de conhecimento sobre acesso vascular definitivo em usuários de hemodiálise (ECAVD) – Cuidados universais, Escala de conhecimento sobre acesso vascular definitivo em usuários de hemodiálise (ECAVD) – Cuidados específicos, Escala de conhecimento sobre acesso vascular definitivo em usuários de hemodiálise (ECAVD) – Exame físico e Escala de conhecimento sobre acesso vascular definitivo em usuários de hemodiálise (ECAVD) – Vigilância hemodinâmica. A coleta de dados ocorreu nos meses de fevereiro a agosto de 2013, por meio de um questionário, composto das seguintes partes: julgamento do conteúdo (constructo), dos atributos e dos componentes de cada escala construída. A validação de conteúdo das escalas foi realizada por doze juízes, com ampla experiência na área de nefrologia. Todas as escalas construídas foram validadas pelos profissionais, sob consenso favorável mínimo de 75%. Ressalta-se que após validação as escalas foram aplicadas a 84 profissionais de enfermagem que atuam em terapia de substituição renal em 3 centros no interior do Estado de São Paulo, onde 2,3% dos profissionais demonstraram apresentar pouco conhecimento, 33,3% ...
Keywords: Insuficiencia renal cronica; Equipe de enfermagem; Hemodialise; Nefrologia; Cirurgia vascular; Kidneys Diseases